Carotid Occlusion Associated With Eosinophilia and Proteinuria: Potential Diagnostic Clues or Red Herrings?. Issue 1 (June 2022) - Elavarasi, Arunmozhimaran; Narayan, Sunil K.; Parameswaran, Sreejith; Gocchait, Debasis
Nephrotic syndrome and hypereosinophilic syndrome both are uncommon causes of arterial stroke. We had a young patient with internal carotid artery occlusion, who had both these rare associations and was found to have membranous nephropathy. Idiopathic hypereosinophilia was treated with corticosteroids and conventional parasiticidal therapy with the intention of bringing down the eosinophil count. Nephrotic syndrome was also treated with corticosteroids and immunosuppression with cyclophosphamide. Hematologic abnormalities are an important cause of arterial thrombosis with effective secondary prevention strategies. Similarly, nephrotic syndrome is not to be missed as early treatment may prevent vascular complications. While cause-effect associations remained presumptive and a single diagnostic label elusive, the patient was recognized and treated early and had a good prognosis. However, other common causes of stroke should always be worked up for, and vigilant follow-up mandatory for prevention and treatment of recurrences which can have devastating sequelae such as total blindness and other vascular outcomes.